Expressing evidentiality in Lithuanian - Ruskan, Anna (Lietuvių kalba, 2010)
Evidentiality in Lithuanian, like in some other European languages, can be expressed both grammatically and lexically; a large inventory of grammatical and lexical means make up a continuum, which is introduced and defined by B. Wiemer (2008). Constructions based on active and passive participles that function in the main clause as predicates are regarded as grammatical markers of evidentiality while parentheticals (e. g. matyt, girdi), particles (e. g. esą, neva, tarsi) and adverbs (e. g. akivaizdžiai, aiškiai) can be qualified as lexical. There are also evidential markers that take an intermediate position in the continuum of lexical and grammatical means. While the evidential constructions based on participial morphology have been thoroughly researched in Lithuanian linguistics, the exploration of lexical markers of evidentiality is fairly new and its inventory has not been fully identified and described yet. The main sources of lexical evidential markers are verbs, neuter adjectives, nouns, adverbs related to perception, cognition or communication. The integration of lexical markers into the study of evidentiality helps to see the coding of the source of information in language more holistically as well as to more precisely describe the structure of lexical and grammatical markers, shades of meaning and their development.